Increased fucoxanthin in Chaetoceros calcitrans extract exacerbates apoptosis in liver cancer cells via multiple targeted cellular pathways, - Su, Chern Foo; Md. Yusoff, Fatimah; Umar Imam, Mustapha; Jhi, Biau Foo; Ismail, Nor Sharina; Azmi, Nur Hanisah; Yin, Sim Tor; Khong, Nicholas Mun Hoe; Ismail, Maznah (Elsevier BV, 2019)
In this study, anti-proliferative effects of C. calcitrans extract and its fucoxanthin rich fraction (FxRF) were assessed on human liver HepG2 cancer cell line. Efficacy from each extract was determined by cytotoxicity assay, morphological observation, and cell cycle analysis. Mechanisms of action observed were evaluated using multiplex gene expression analysis. Results showed that CME and FxRF induced cytotoxicity to HepG2 cells in a dose and time-dependent manner. FxRF (IC50: 18.89 μg.mL−1) was found to be significantly more potent than CME (IC50: 87.5 μg.mL−1) (p < 0.05). Gene expression studies revealed that anti-proliferative effects in treated cells by C. calcitrans extracts were mediated partly through the modulation of numerous genes involved in cell signaling (AKT1, ERK1/2, JNK), apoptosis (BAX, BID, Bcl-2, APAF, CYCS) and oxidative stress (SOD1, SOD2, CAT). Overall, C. calcitrans extracts demonstrated effective intervention against HepG2 cancer cells where enhanced apoptotic activities were observed with increased fucoxanthin content.